Colloquies on European Civil Procedure : Exploring the ELI-UNIDROIT Model European Rules of Civil Procedure - Benito, Marco de (International Law E-books Online, Collection 2026., 2025)
This volume brings law to life through a free and lively dialogue on the new Model European Rules of Civil Procedure. In it, some of Europe's leading jurists engage in a free-wheeling discussion of the most important issues in procedural law today. With its elegant style and unconventional intellectual approach, Colloquies stands out as a rare gem of comparative legal literature.